Sugarcane bagasse ash as a partial-portland-cementreplacement material (2010)
This investigation is focused on the evaluation of the effects of the partial replacement of Portland cement by sugar cane bagasse ash (CBC) in mortars. The main objective wasto find a suitable destination for an agricultural residue generated in an increasing amount in Brazil, as the use of CBC as a mineral admixture in mortars and concretes, contributes to decrease the environmental impact of these materials related to cement production. Experimental techniques were applied both for the CBC characterization and for the evaluation of its use as a mineral admixture in mortars, based on mechanical and physical tests. The results from tests with mortars indicated the viability of the partial substitution of cement by up to 20% of the CBC considered.